1999
DOI: 10.1530/eje.0.1410325
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 1-year treatment with interferon-beta1b on thyroid function and autoimmunity in patients with multiple sclerosis

Abstract: Objective: Interferon-b (IFN-b) is a widely used therapy for multiple sclerosis (MS), a demyelinating disease of the central nervous system. This study has evaluated the effect on thyroid function and autoimmunity of a 1-year treatment with IFN-b1b in patients with MS. Patients: We studied 31 patients (age 34 Ϯ 7 years, 21 women) with relapsing-remitting MS during IFN-b1b treatment of 1 year duration. Systematic thyroid assessment and measurements of serum interleukin-6 (IL-6) levels were performed at baseline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
2
3

Year Published

2000
2000
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 25 publications
1
24
2
3
Order By: Relevance
“…Thyroid autoimmunity following the treatment of multiple sclerosis is not confined to the use of Campath-1H. Some [18,49,56], but not all [18,64] authors report a significant increase in anti-thyroid microsomal antibodies after starting IFN-β. There is one case report of Graves' disease after treatment with glatiramer acetate [27].…”
Section: Discussionmentioning
confidence: 99%
“…Thyroid autoimmunity following the treatment of multiple sclerosis is not confined to the use of Campath-1H. Some [18,49,56], but not all [18,64] authors report a significant increase in anti-thyroid microsomal antibodies after starting IFN-β. There is one case report of Graves' disease after treatment with glatiramer acetate [27].…”
Section: Discussionmentioning
confidence: 99%
“…IFN thus appeared to trigger organ-specific autoimmune diseases in our patient. Exacerbation of autoimmune phenomena has been frequently reported with IFN (12)(13)(14)(15) but not for IFN (16), but both share a common receptor. Dayal et al (17) reported that IFN-secreting cells increased in the early course of IFN therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Thyroid autoimmunity is not confined to treatment with Campath-1H. A number of authors [26][27][28] , but not all [29] , report a significant increase in anti-thyroid microsomal antibodies after starting interferon-␤ . There is also 1 case report of Graves' disease following treatment with glatiramer acetate [30] .…”
Section: Autoimmunitymentioning
confidence: 99%